From floundering to fluent reaching and teaching struggling readers - Young, Nicholas D. 1967; Michael, Christine N.; Citro, Teresa Allissa (Lanham Rowman & Littlefield, 2018)
"This book primarily focuses on gaining a deeper understanding of the kinds of difficulties that can attend the reading process, especially for at-risk readers and those with reading disabilities"--Provided by publisher.
Wrestling with reading: understanding the basics of reading disorders and challenges / Nicholas D. Young & Christine N. Michael -- Spotting problems before they start: preventing and remediating reading difficulties / Jade Wexler, Jeanne Wanzek & Sharon Vaughn -- Understanding and promoting the motivation to read in young children / Elizabeth Jean, Paul L. Morgan, and Douglas Fuchs -- Designing successful reading comprehension programs: promising instructional strategies and practices / Nicholas D. Young, and Kristen Bonanno-Sotiropoulos -- Reading in the 21st century: utilizing digital literacy practices and assessments to help struggling secondary readers / Melissa A. Mumby and Nicholas D. Young -- The power of peers: using peer-assisted learning strategies to reverse Matthew effects in reading / Paul Morgan, Caressa Young, Douglas Fuchs and Kristen Bonanno-Sotiropoulos -- Connecting in the classroom: collaborative strategic reading for students with learning disabilities / Alison Boardman, Sharon Vaughn & Janette Klinger -- Beyond the schoolhouse door: promoting reading partnerships in the home and community / Christine N. Michael & Nicholas D. Young.
Includes bibliographical references.
Keywords: Reading disability; Reading -- Remedial teaching